Análise de circulação hidrodinâmica e de qualidade de água no sistema estuarino do Rio Paraíba do Norte, PB - Silva, Larissa Maia Dantas da (2019)
Estuarine systems are dynamic environments that are under constant anthropic influence. The uses of its margins are potential polluters when in disagreement with quality standards. The climatic, hydro biological and geographical conditions make the Paraíba do Norte river estuary and the Northeast of Brazil stand out as to the industrial development in its margins, being the growth of shrimp in captivity the most important activity. For this reason, this study proposes, using computational modeling, to understand how an estuarine system that has a split margin between mangroves and shrimp farms reacts, in terms of water quality, to the pressures to which it is exposed. In order to do this, the models of the SisBaHiA® were used, where studies of hydrodynamic circulation patterns, mangrove flooding and drying processes, and the influence of the harvesting on OD and BOD parameters. By simulating scenarios with seasonal variability and different effluent loads, it was possible to analyze in a comparative way the behavior of the estuary. The circulation of the estuary is dominated by the tides and its currents are more intense during the ebb period, due to the influence of the tide plains. The temporal results showed that during the river flood time, the OD and BOD conditions of the estuary are more affected, since the load of these parameters reaching the estuary is high. During droughts, effluents tend to be trapped in the estuary, while in floods it also remains in the coastal region. Spatially, regions with smaller flows, such as the coastal areas and the Mandacaru, Tambiá and Sanhauá Rivers, have lower concentrations of OD and higher BOD, due to the reduced rate of renewal of these sites. Finally, shrimp farming, even under extreme conditions, does not have an impact on OD and BOD conditions comparable to river inputs.